Impact of Cervical Cancer on Women’s Bio-Psycho-Social Aspects of Health: A Mixed Methods Study - Roaa Kareem Bzeipez, Sadeq Al-Fayyadh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervical cancer is the second most common type of cancer affecting women worldwide. Sexual and reproductive problems can reduce the quality of life of women with cervical cancer. Quality of life studies in health care industry, especially in oncology, have become an essential tool used to assess patient resilience in different types of cancer and different treatment modalities. Aim(s) to identify the impact of cervical cancer on women’s physical, psychological and social health by examining quality of life and to discover any possible statistically significant relationship between women’s quality of life and some social, demographic and reproductive characteristics. And explore the experience of women with cervical cancer in terms of its impact on physical, psychological and social health. Methods: A convergent design was used in this study. A mixed-method design was used in this study that consists of The EORTC QLQ-C30 and EORTC QLQ-CX24and semi-structured interviews guide for the quantitative section.100 married women who suffer from cervical cancer and who visit the oncology centers in the city of Baghdad from 14th September to 2nd December2021.Regarding the qualitative section an eleven interview. Results: The quantitative study showed that Cancer had a profound impact on the dimensions of the physical, psychological and social life of a woman with cervical cancer. Similarly, the qualitative findings showed that the life experience of women with cervical cancer has endured a lot of suffering of fighting the disease and its management-related consequences. However, faith-based resilience was the defense mechanism that can explains women’s capacity to move on with their life living with cancer Keywords: Quality of Life; Cervical Cancer; Cancer; Gynecological Cancer; Women’s Health